Guru dan Pengembangan Kurikulum Pendidikan Agama Islam di Era Revolusi Industri 4.0 - Aldo Redho Syam (State Islamic Institute of Madura, 2019)
In facing the dynamics of social change in the era of industrial revolution 4.0, especially Islamic education, the existence and role of teachers in developing Islamic religious education curricula became very important, so that the compilation of Islamic religious education curriculum in accordance with the characteristics, mission, and vision of Islamic education institutions, and in accordance with the learning experience needed by students. The development of the Islamic religious education curriculum shows that the education system is dynamic, if the education system does not want to fall into stagnation, then the changes need to be carried out by the teacher and is a must to be carried out in various ways that are innovative, creative, and productive, especially in determining the method, and what strategies will be developed, and how to measure success